Optimization of surface roughness and tool wear on AISI 4140 using coated Ni-YSZ for CNC turning process - Alias, Mohd; M. H. L., Adnan; Nor Bahiyah, Baba; Zainal Ariffin, Selamat; Ahmad Nasser, Mohd Rose; Saiful Bahri, Mohamed (IOP Publishing, 2020)
Numerous type of cutting tools has been developed continuously for use in metal cutting and the coated cemented carbides are the most popular in employing many machining strategies to improve machinability of alloy steel. This paper presents on analyze of surface roughness and tool wear on AISI 4140 alloy steel using CNC lathe machine at various machining parameters such as cutting speed, feed rate and depth of cut. Experiments were conducted using Response Surface Methodology (RSM) and the interactions of machining parameters were analyzed using Analysis of Variance (ANOVA) method. Results showed that the best surface roughness parameter for Ni-YSZ coated tool is at maximum cutting speed, feed rate is minimum and minimum depth of cut which representing 0.28 μm . Whereas, for the tool wear, the best parameter is at minimum cutting speed, minimum feed rate and minimum depth of cut for producing 0.892 μm.